Effect of Tele-nursing on Blood Glucose Control among the Elderly with Diabetes: A Randomized Controlled Trial - Ali Ravari; Alireza sheikhoshaqi; Tayebeh Mirzaei; Mohadeseh Raeisi; Elham Hassanshahi; Zahra Kamiab (Mashhad University of Medical Sciences, 2021)
Background: Diabetes is one of the most common debilitating diseases in the elderly requiring reasonable blood sugar control to prevent complications. Telenursing has been presented as a cost-effective method to control blood glucose levels. Aim: This study aimed to investigate the effect of tele-nursing on blood glucose control in the elderly with diabetes.   Method: This clinical trial study was performed on diabetic elderly referring to the diabetes clinic in Rafsanjan City, Kerman Province, Iran. The participants (n=80) were randomly selected and randomly divided into the intervention and control groups. The intervention group was followed up via phone for 3 months. However, the control group received the intervention provided in the clinic. In addition to demographic characteristics and variables of diabetic patients, the fasting blood sugar (FBS) and glycated hemoglobin (HbA1c) were measured at the baseline and 3 months after the interventions. Results: Before the intervention, the mean FBS and HbA1c of both groups showed no significant difference; nevertheless, there was a considerable difference after the intervention. Paired t-test showed that after the intervention, the amounts of FBS and HbA1c were reduced to 33.92±21.51 and 1.51±0.86, respectively. Implications for Practice: Our results indicated that the use of tele-nursing in elderly patients with diabetes was an effective strategy that led to increased self-care, and consequently, control of blood sugar.